Improving the publication activity of Ukrainian scientists: problems, solutions, the use of mathematical and statistical methods - S. O. Serbenyuk (Law and Safety)
Many Ukrainian and foreign scholars have been studying the problems of financing scientific activities for a long time. Moreover, such issues are even raised in the works of scholars from developed Western countries. The range of such studies is extremely wide: from analysing problems and violations of the above-mentioned principles of law to modelling innovative grant support systems, including those that model an equal and fair system. Foreign scientists mostly focus on the specifics of grant provision and its impact, improvement and innovation of the financial resource allocation system in the field of science, etc. In Ukraine, the vast majority of research is concerned with the comparative characteristics of the share of the gross domestic product allocated to science funding, general problems of international cooperation with foreign grant providers, improvement of the system of financial resources allocation in the field of science, etc. Unfortunately, no attention has been paid to specific mechanisms of rewarding publications in leading foreign scientific journals. This issue is no less important, since individual support for publication activity is a powerful “lever of encouragement” for researchers and academic staff, which directly affects the results of a particular institution in the chain of international and national rankings. In addition, such support contributes to the development of science, scientific and technological progress, and raises the country’s rating in the international arena.